1966
DOI: 10.2172/4523867
|View full text |Cite
|
Sign up to set email alerts
|

Atr Fuel Materials Development Irradiation Results. Part Ii

Abstract: This report w88 prepared 88 an account of Government sponsored work. Neither the United States, nor the Commission. nor any person acting on behalf of the Commisslon:A. Makes any warranty o r representation, expressed or implied, with respect to the accuracy. cornpleteneea, or usefulness of the Information contained in this report. or that the use of any information, apparatus. method. or process dlsclosed in this report may not infringe privately owned rights: or B. Assumes any liabilitles with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This work focuses on the Mark VII fuel design. Information related to legacy fuel forms is considered only as needed to supplement the Mark VII fuel literature [13][14][15]. An ongoing effort is under way to convert the ATR core to low-enriched uranium (LEU) [16,17].…”
Section: Advanced Test Reactor Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…This work focuses on the Mark VII fuel design. Information related to legacy fuel forms is considered only as needed to supplement the Mark VII fuel literature [13][14][15]. An ongoing effort is under way to convert the ATR core to low-enriched uranium (LEU) [16,17].…”
Section: Advanced Test Reactor Fuelmentioning
confidence: 99%
“…A later study published in 1958 reported that the stable uranium aluminides include UAl 2 , UAl 3 , and UAl 4 [20]. The discrepancy may be related to crystalline defects in the UAl 4 lattice, which displace U atoms and produce a U:Al stoichiometry closer to 1:5 [14]. Uranium aluminides are prepared by vacuum induction melting, arc melting, casting, or reaction of uranium hydride with Al [11,18].…”
Section: Fabricationmentioning
confidence: 99%
“…In view of these new parameters in fuel element operation, it was believed that an irradiation test program was worthwhile. A similar program directed toward the needs of the Advanced Test Reactor (ATR) and the High Flux Isotope Reactor (HFIR) had just been completed [2], and space was available in the irradiation facility used for this test. The ATR and HFIR fuel elements use aluminum clad dispersion-type fuel elements.…”
mentioning
confidence: 99%